Khan Barak Coins of the XV Century of the Bulgarian Mint (based on the materials of the hoard "Karaulnaya Gora") - Bugarchev Aleksei I.; Petrov Pavel N.; Singatullina Alfira Z.; Shaykhutdinova Eugenia F. (Археология евразийских степей, 2022)
One of the most important hoard complexes of the beginning of the XV century for the study of coinage in the Bulgar land is the treasure of coins "Karaulnaya Gora", stored in the National Museum of the Republic of Tatarstan in Kazan. The hoard was found in 1957 near the village of Karaulnaya Gora in the Oktyabrsky district of Tatarstan. It consists of 2,859 silver coins, beaten on behalf of the khans, from Shadibek to Muhammad and Giyas ad-Din, including Muhammad Barak. Since the number of Bulgar silver coins of Barak in the treasure turned out to be quite sufficient for statistical research (109 akche of Bulgar coinage and 20 dirhams of southern coinage), these coins were the initial and basic starting point for studying. It is known that Bulgar-types of Barak were minted in 1422–1425. Based on the study of the legends on the front sides of coins, four typological groups were identified. As a result of the study, it was found that the weight of the coins tends to 0.52 g. The results of the analysis of the surface layer of the akche Barrack are given – silver 62–87%, copper 9–34%. The authors believe that the metrological features of the Bulgar Barak issues will allow to attribute numerous regional coins with the name of Muhammad, minted in 1419–1430.